SISTEM INFORMASI SEBAGAI MEDIA PROMOSI DAN PEMASARAN PADA CV. ANUGRAH SINAR ABADI - Sany, Ezrifal (FORTECH (Journal of Information Technology), 2020)
Means of the internet is one of the effective and efficient information media in the delivery of information that can also be accessed by anyone, anytime and anywhere. Internet media is very influential in the world of business and commerce. Internet facilities are increasingly developing, it is very possible for people to get information so that accessing information can be done anywhere and anytime because it is not limited by space and time. CV. Anugrah Sinar Abadi is one of the companies in Jambi, this company is in the field of marine commodities, especially fish. Competition between companies engaged in the same field is very tight, especially in the field of marketing and promotion, to improve company services, it is necessary to use information technology in marketing and promotion, as a tool in sales using web media so as to provide efficiency and effectiveness in operations, time , places and information for customer service.